Cardiopulmonary exercise testing has greater prognostic value than sarcopenia in oesophago‐gastric cancer patients undergoing neoadjuvant therapy and surgical resection. Issue 8 (31st August 2021) - West, Malcolm A; Baker, William CA; Rahman, Saqib; Munro, Alicia; Jack, Sandy; Grocott, Michael PW; Underwood, Timothy J; Levett, Denny ZH
Abstract: Background: Sarcopenia (low skeletal muscle mass), myosteatosis (low skeletal muscle radiation‐attenuation) and fitness are independently associated with postoperative outcomes in oesophago‐gastric cancer. This study aimed to investigate (1) the effect of neoadjuvant therapy (NAT) on sarcopenia, myosteatosis and cardiopulmonary exercise testing (CPET), (2) the relationship between these parameters, and (3) their association with postoperative morbidity and survival. Methods: Body composition analysis used single slice computed tomography (CT) images from chest (superior to aortic arch) and abdominal CT scans (third lumbar vertebrae). Oxygen uptake at anaerobic threshold (VO2 at AT) and at peak exercise (VO2 Peak) were measured using CPET. Measurements were performed before and after NAT and an adjusted regression model assessed their association. Results: Of the 184 patients recruited, 100 underwent surgical resection. Following NAT skeletal muscle mass, radiation‐attenuation and fitness reduced significantly ( p < 0.001). When adjusted for age, sex, and body mass index, only pectoralis muscle mass was associated with VO2 Peak ( p = 0.001). VO2 at AT and Peak were associated with 1‐year survival, while neither sarcopenia nor myosteatosis were associated with morbidity or survival. Conclusion: Skeletal muscle and CPET variables reduced following NAT and were positively associated with each other. Cardiorespiratory function significantly contributes to short‐term survival after oesophago‐gastric cancer surgery.